2021
DOI: 10.1080/17482631.2021.1901449
|View full text |Cite
|
Sign up to set email alerts
|

Caring approach for patients with chest pain – Swedish registered nurses’ lived experiences in Emergency Medical Services

Abstract: Purpose: Encountering patients with chest pain is common for Registered Nurses (RNs) in Emergency Medical Services (EMS) who are responsible for the patient's medical and nursing care . From a lifeworld perspective, bodily illness is related to existential suffering, requiring knowledge to asses the situation from a holistic perspective . The aim of this study is to describe the caring approach when RNs encounter patients with chest pain. Methods: A phenomenological methodology to capture RNs' lived experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Fostering trust, care and patient empowerment were perceived as important by ambulance clinicians when managing adults suffering pain. It was found that “ Having a calm approach while encountering patients with chest pain is experienced as a prerequisite in obtaining the patient's trust .” Carnesten et al 29 [researcher quotation]. Creating conditions of participation and adapting to the patient's needs were methods identified to promote patient empowerment 40 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fostering trust, care and patient empowerment were perceived as important by ambulance clinicians when managing adults suffering pain. It was found that “ Having a calm approach while encountering patients with chest pain is experienced as a prerequisite in obtaining the patient's trust .” Carnesten et al 29 [researcher quotation]. Creating conditions of participation and adapting to the patient's needs were methods identified to promote patient empowerment 40 …”
Section: Resultsmentioning
confidence: 99%
“…Regular re‐evaluation of pain was deemed important as well as allowing the patient to choose additional analgesic administration where needed 40 . Good verbal and nonverbal communication was found to engender well‐being, trust, confidence, and reassurance for patients 29 . Professional behavior and conduct were also a key aspect of care, as prioritization of the tasks over and above the patient were deemed to have a negative impact on the patient, creating a sense of loneliness 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Older persons' dignity is also honoured when supported in making care decisions despite lowered decision-making ability [32]. However, ambulance personnel's decisions on-scene are influenced by the risk of being held liable in case of medical error [33], and the ability to provide qualitative safe care is similarly dependent on the collaboration within the ambulance team [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Ambulance personnel describe wanting available external dialogue with other healthcare professional during decision-making (159). Support is further experienced by ambulance personnel in external dialogue with colleagues during assessments and level-of-care decisions (114,159,307). Moreover, ambulance personnel seek acknowledgement of their decisions (23,168) through, for example dialogues with colleagues or other healthcare professionals during decision-making involving complex decisions.…”
Section: Healthcare Professionals' Experiences Of External Dialogue I...mentioning
confidence: 99%